Removal of Pb(II) from water using a bio-composite adsorbent-A systematic approach of optimizing synthesis and process parameters by response surface methodology. (1st March 2018) - Maity, Jayabrata; Ray, Samit Kumar
Abstract: The synthesis parameters for preparing a novel bio-composite adsorbent by integrating a copolymer of 2-hydroxyethyl methacrylate (HEMA), acrylamide (AM) and crosslinker N, N ′-methylene bis acrylamide (MBA), polyethylene glycol (PEG) and Azadirachta Indica or Neem leaf (NL) and the process parameters for its subsequent use for adsorption of Pb(II) ion from water were optimized with central composite design (CCD) of response surface methodology (RSM). The structure of the bio-composite was characterized by FTIR, XRD, TGA, DMA, FESEM-EDX and PZC analysis. The optimized adsorbent prepared with a AM: HEMA molar ratio of 5:1, MBA, PEG and NL wt% of 0.75, 4 and 2.5, respectively showed 182.85 mg/g (92.5%) adsorption of Pb(II) from water containing low concentration of 50 mg/L of Pb(II) ion and 911 mg/L (57%) adsorption of the same metal ion for a high feed concentration of 400 mg/L in a solution pH of 6, adsorbent dose of 0.25 g/L and a feed temperature of 30 °C. This functional bio-composite may also be suitably used for separation of other metal ions and polar molecules from water. Graphical abstract: Image 1 Highlights: Adsorbents were made by integrating acrylic monomers, neem leaf and PEG. The adsorbents were characterized by FTIR, XRD, FESEM-EDX, DMA, TGA. Pb(II) adsorption from water were evaluated with these adsorbents. Synthesis and process parameters were optimized with CCD of RSM. The adsorbents showed high adsorption and removal% of Pb(II).